Complex joint investigations in the sphere of theory and technology of metallurgical production as one of the directions of integration processes - O. V. Dubina; V. I. Timoshpolsky; A. K. Golubchenko; V. I. Gubinsky; B. S. Soroka; M. P. Revun; J. S. Postolnik; V. V. Filippov; V. M. Olshansky; I. A. Trusova (Литьë и металлургия, 2001)
.